Engineering of biomolecules by bacteriophage directed evolution. (June 2018) - Brödel, Andreas K; Isalan, Mark; Jaramillo, Alfonso
Graphical abstract: Highlights: Directed evolution systems based on conditional phage replication (CPR) expand the potential of protein engineering. CPR platforms function in both batch and continuous culture. CPR systems bypass key limitations of conventional phage display. Directed evolution of a wide range of proteins can be achieved by CPR. Abstract : Conventional in vivo directed evolution methods have primarily linked the biomolecule's activity to bacterial cell growth. Recent developments instead rely on the conditional growth of bacteriophages (phages), viruses that infect and replicate within bacteria. Here we review recent phage-based selection systems for in vivo directed evolution. These approaches have been applied to evolve a wide range of proteins including transcription factors, polymerases, proteases, DNA-binding proteins, and protein–protein interactions. Advances in this field expand the possible applications of protein and RNA engineering. This will ultimately result in new biomolecules with tailor-made properties, as well as giving us a better understanding of basic evolutionary processes.